Peran Motivasi Kerja sebagai Mediator dalam Hubungan Beban Kerja dan Stres Kerja terhadap Kinerja Karyawan di Rumah Sakit Cempaka Lima Banda Aceh - Darnia Darnia; Lukman Ibrahim; Kurnia Asni (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2026)
This study aims to analyze the effects of workload and job stress on employee performance, with work motivation serving as a mediating variable, at Cempaka Lima Hospital, Banda Aceh. The study employed a quantitative approach using an explanatory research design. The research population consisted of all hospital employees, with a sample of 145 respondents selected through proportionate stratified random sampling. Data were collected using a structured questionnaire based on a five-point Likert scale and analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach with SmartPLS software. The findings reveal that workload does not have a significant direct effect on employee performance; however, it has a positive and significant effect on work motivation. Furthermore, work motivation has a very strong and significant positive effect on employee performance. In contrast, job stress does not have a significant effect on either work motivation or employee performance. The indirect effect analysis indicates that work motivation significantly mediates the relationship between workload and employee performance, but it does not mediate the relationship between job stress and employee performance. These findings suggest that employee performance in the healthcare sector is influenced more by internal factors, particularly work motivation, than by external factors such as workload and job stress. Therefore, hospital management should prioritize strategies aimed at enhancing employees' work motivation to achieve optimal and sustainable performance.